Strategi Meningkatkan Prestasi Belajar Siswa pada Pembelajaran Pendidikan Agama Islam di SMP Muhammadiyah 1 Wonosobo - Alfina Isnawati; Ahmad Zuhdi; Salis Irvan Faudi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
. This study aims to determine the strategie used to improve student learning achievement in Islamic Religious Education at SMP Muhmmadiyah 1 Wonosobo. By focusing on internal an external factos, this study is based on the improtance of the teacher’s role in designing and implementing effective learning strategies so that the teaching and learning process can run optimally and have an impact on improving student learning achievement. This study uses a qualitative approach with a descriptive research type. Data collection teachniques include observation, inerviews, and documentation. The results show that the strategies implemented by teachers include the use of veried learning methods, learning motivaton, utilization of learning media, and instilling religious values in everyday life. These strategies have been proven to be able to increase student interest, motivation, and learning achievement in Islamic Religious Education subject. In a conducive learning process, there are major challenges such as low student interestt in learning and the existence of a dual curricullum. Therefore, supporting factors are needed, namely support from the school and a conductive learning environment. Meanwhile, inhibiting factors include limited learning time differences in student abilities, anda incompatibility of parenting patterns between the school and parents. Thus, the application of appropriate lerning strategies has a significant impact on improving student learning achievement.